Hypertension and Stroke: Update on Treatment - Mauricio Wajngarten; Gisele Sampaio Silva (European Cardiology Review, 2019)
Stroke is the second most common cause of mortality worldwide and the third most common cause of disability. Hypertension is the most prevalent risk factor for stroke. Stroke causes and haemodynamic consequences are heterogeneous which makes the management of blood pressure in stroke patients complex requiring an accurate diagnosis and precise definition of therapeutic goals. In this article, the authors provide an updated review on the management of arterial hypertension to prevent the first episode and the recurrence. They also present a discussion on blood pressure management in hypertensive urgencies and emergencies, especially in the acute phase of hypertensive encephalopathy, ischaemic stroke and haemorrhagic stroke.